Penerapan Algoritma Linear Congruent Method (LCM) Dalam Pengacakan Soal Ujian Online Penerimaan Siswa Baru Berbasis Web - Manaon Hasibuan, Tongku; Muhtar Safari, Dede (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Examination is one of the processes to determine the achievement of ability and success in understanding the field of study taken by each student. Exams are not only carried out by students who have received lessons, but exams are also carried out by students to enter certain schools. Some schools in Indonesia still conduct conventional exams and can be said to be less effective or efficient in any way. As technology develops, the implementation of new student admission exams or the implementation of semester exams is carried out online because it can be the right solution to get a more effective and efficient exam implementation. However, online exams still cause the same questions that are displayed to each examinee. This can trigger dishonesty of examinees in the examination process. One way to minimize cheating and the similarity of these questions, the right solution is to create a web-based online exam application using the Linear Congruent Method (LCM) algorithm method because this algorithm can randomize exam questions for each examinee, so that each examinee gets a different question.